Intrauterine Infusion of Human Platelet-Rich Plasma Improves Endometrial Regeneration and Pregnancy Outcomes in a Murine Model of Asherman’s Syndrome - Kim, Ji Hye; Park, Mira; Paek, Jin Young; Lee, Woo-Sik; Song, Haengseok; Lyu, Sang Woo (Frontiers in Physiology, 2020)
Asherman syndrome (AS) is characterized by intrauterine adhesion or fibrosis resulting from damage to the endometrium, often leading to amenorrhea, infertility, or recurrent pregnancy loss. Although various therapeutic strategies for AS have been proposed, the options remain limited. New strategies such as bone marrow-derived mesenchymal stem cell (BM-MSC) therapy aim to potentiate the intrinsic capacity of endometrial regeneration. However, BM-MSC therapy has not been widely adopted mainly because it involves invasive and expensive procedures such as bone marrow biopsy and cell storing. On the other hand, platelet-rich plasma (PRP) is considered safe and affordable because it involves the less invasive procedure of blood collection from peripheral veins to produce PRP. To assess the effectiveness of human PRP infusion for endometrial regeneration, we established a murine model of injury-induced AS and evaluated endometrial morphology, expression of fibrosis-related factors, implantation sites (IS), and pregnancy outcomes associated with human PRP treatment. We found that treatment with human PRP was associated with improved endometrial morphology, reduced degree of fibrosis, and down-regulated expression of fibrosis-related factors in murine model of AS. Furthermore, human PRP treatment was associated with a higher number of IS and live-births. Our results suggest that human PRP treatment may become a valuable strategy to promote the regeneration of damaged endometrium and thus improve fertility and pregnancy outcomes in clinical practice.